Examining the training design and training transfer of a boundary management training: A randomized controlled intervention study - Kathrin Reinke; Sandra Ohly (Journal of Occupational and Organizational Psychology, 2024)
In our mobile working world, boundaries between work and non-work domains are more and more blurred, which can impair professionals' recovery and well-being. Consequently, managing work–non-work boundaries represents an important challenge for professionals. Research suggests that boundary work tactics conveyed in boundary management interventions may promote recovery and well-being. However, the efficacy of boundary work tactics is largely unknown, as well as theoretical mechanisms that may explain the effectiveness of boundary management interventions in regard of both training design and training transfer. Building on the social cognitive theory of self-regulation, we develop a web-based boundary management training. Based on the integrated training transfer and effectiveness model, we evaluate its effects on the three levels of training effectiveness: (1) perceived learning, (2) cognitions and behaviours, with boundary control and boundary creation as indicators, and (3) recovery and well-being. Results of our randomized controlled intervention study show several expected changes in boundary creation, suggesting that drawing on the social cognitive theory of self-regulation for training design can result in effective behaviour change. Intervention effects on recovery and well-being are more ambiguous, hinting at the power but likewise potential limitations of boundary creation.
Keywords: 650; boundary creation; boundary management; intervention study; recovery; training design; training transfer; well-being